The effects of an overnight holding of whole blood at room temperature on haemoglobin modification and in vitro markers of red blood cell aging. Issue 4 (6th March 2015) - Eckstein, M.; Zimmermann, R.; Roth, T.; Hauck‐Dlimi, B.; Strasser, E. F.; Xiang, W.
<x xml:space="preserve">Abstract</x> Background Some effects of the red blood cell (RBC) storage lesion are well documented whereas others are not. Whether a period of room temperature hold (RTH) during RBC production enhances the RBC storage lesion has remained controversial. In this study, we compared whole blood (WB)‐derived RBCs produced after 24‐h RTH with rapidly cooled (RC) RBCs and tested them for classical metabolic markers and signs of oxidative damage. Study design and methods SAGM‐RBCs were prepared from mixed and split pairs (n = 12) of WB units. RBCs prepared after a 24‐h period of RTH on day+1 after collection (RTH‐RBCs) were compared with RC‐RBCs. All RBCs were stored at 4°C for 42 days with assay of in vitro variables on days+1, +15, +22, +29 and +42. The study examined standard quality parameters, glutathione, catalase and superoxide dismutase (SOD) activities, and indicative markers of oxidative cell damage including post‐translational haemoglobin modification, malondialdehyde (MDA), and phosphatidylserine expression. Results RTH‐RBCs exhibited decreased levels of potassium (1·98 ± 0·26 vs. 5·23 ± 0·65 mmol/l) and of 2, 3‐diphosphoglycerate (2, 3‐DPG) on day+1 compared with RC‐RBCs. Haemolysis rate on day+42 was higher in RTH‐RBCs than in RC‐RBCs (0·52 ± 0·13 vs. 0·37 ± 0·12%). The phosphatidylserine expression amounted to 0·25 ± 0·20% in RTH‐RBCs and 0·07 ± 0·12% in RC‐RBCs. Haemoglobin modification was not different between both RBC groups. RTH‐RBCs showed slightly higher MDA concentration on days +29 and +42. Conclusions RC‐RBCs and RTH‐RBCs show only small differences of classical in vitro parameters and no relevant differences in antioxidative metabolism and oxidative haemoglobin modification. These findings do not explain the loss observed in in vivo survival studies with RBCs.